Gender perspectives on agroforestry practices in Mt. Merapi hazards and risks prone area of Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rozaki Z, Rahmawati N, Wijaya O, Safitri F, Senge M, Kamarudin MF. 2021. Gender perspectives on agroforestry practices in Mt. Merapi hazards and risks-prone area of Indonesia. Biodiversitas 22: 2980-2987. Despite the risk and hazards of the Mt. Merapi prone area, people continue to stay in the area as Agroforestry Adopters. This study aims to analyze the gender perspectives on agroforestry (AF) practices in the Mt. Merapi prone area. 128 men and 86 women were randomly selected from four different areas. Descriptive analysis, independent t-test, and logistic multinomial regression were used to analyze the data. Gender issue in AF practices is found in some parts of the practices. For example, women are more predominant in marketing the products rather than men, whilst the men are predominant in activities that need more strength such as planting. An external factor that is significant is the different impacts of farmers support groups on men and women. Meanwhile, factors such as capital access and AF easiness do not show significant differences between men and women. In other words, these two variables are felt the same among men and women when practicing AF. As for the contribution of AF, social aspect is found to show significant differences, whilst economic and ecology do not show significant differences to both the men and women. Additionally, factors that affect the perspectives on AF contribution vary among the respondents across both groups of men and women. This study suggests that the different perspectives and factors that are affecting AF farmers can be used to develop future AF promotion programs.
Keywords: Gender perspectives; Mt. Merapi; agroforestry; Indonesia; hazards and risks